Poverty in Sub-Africa: Reflecting on the Failure of International Global Governance - Gwandu, Hassan Attahiru (Studia Historiae Oeconomicae, 2022)
The paper studies the phenomenon of poverty in underdeveloped/third-world countries, particularly within the context and the failure of international organizations in Sub-Saharan Africa. The article analyzes that the increasing problem of poverty in the region’s countries/Africa is a replication of the failure of the organizations such as the IMF and the World Bank policies such countries. Despite some projects such as Millennium Development Goals (MDG), Sustainable Development Goals (SDG), and many more by the United Nations. Many of these programs have failed to eradicate or reduce poverty. Instead, the situation has worsened most, especially in Africa, where the rate of poverty is increasing, with several regions in the continent experiencing the worse hunger epidemic in recent times. Therefore, the research posits that the failure of international institutions, the World Bank, and IMF policies have immensely become a significant contributing factor to the poverty level in Sub-Saharan Africa.